Ten‐year longitudinal analysis of hydroxyurea implementation in a pediatric sickle cell program. (2nd September 2022) - Phan, Vivian; Park, Ju Ae; Dulman, Robin; Lewis, Angela; Briere, Noravy; Notarangelo, Bailey; Yang, Elizabeth
Abstract: Hydroxyurea (HU) has proven benefit in sickle cell anemia (SCA), but HU is still underutilized. The Pediatric Sickle Cell Program of Northern Virginia prescribes HU regardless of symptoms to all SCA patients age ≥ 9 months and prospectively tracks outcomes. HU is dosed to maximum tolerated dosing (MTD), targeting 30% Hgb F. Longitudinal data from 2009 to 2019 encompassing 1222 HU‐eligible and 950 HU‐exposure patient‐years were analyzed in 2‐year intervals for hemoglobin (Hgb), fetal hemoglobin (Hgb F), hospitalizations, transfusions, and treat‐and‐release ED visits. Comparing HU‐eligible patients in the interval prior to HU implementation (2009–2011) to the last interval analyzed after HU implementation (2017–2019), HU usage increased from 33% to 93%, average Hgb increased from 8.3 ± 0.98 to 9.8 ± 1.3 g/dl ( p  < .0001), average Hgb F rose from 13 ± 8.7% to 26 ± 9.9% ( p  < .0001), hospitalizations decreased from 0.71 (95% CI 0.54–0.91) to 0.2 (95% CI 0.13–0.28) admissions/person‐year, sporadic transfusions decreased from 0.4 (95% CI 0.27–0.55) to 0.05 (95% CI 0.02–0.12) transfusions/person‐year. Treat‐and‐release ED visit rates remained unchanged, varying between 0.49 (95% CI 0.36–0.64) and 0.64 (95% CI 0.48–0.83) visits/person‐year. By the last interval, 72% of patients had Hgb ≥ 9 g/dl, 42% had Hgb F ≥ 30%, 79% experienced no hospitalizations, and 94% received no transfusions. Uniform HU prescription for SCA patients with close monitoring to achieve high Hgb F resulted in significant improvements in laboratory and clinical outcomes within 2 years, which continued to improve over the next 6 years. Rigorous HU implementation in a pediatric sickle cell population is feasible, effective, and sustainable.